How Much Do Mergers and Acquisitions Improve Performance: Case Study Albanian Banks - Barbullushi, Erjola; Kastrati, Albana (The Journal of Accounting and Management, 2025)
Mergers and acquisitions in the banking sector are strategic tools to strengthen and unite banks. These strategies ensure increased business, talent, and skills from other banks, as well as increased profitability. Objectives: This study investigates the impact of mergers and acquisitions (M&A) on the financial performance of banks in Albania, a country with a dynamic but competitive banking environment. M&A are explored as strategic tools to enhance efficiency, profitability, and market positioning. Prior Work: Previous research presents mixed findings on the effect of M&A on banks’ performance, with studies across various countries and sectors showing both improvements and drawbacks in key financial metrics post-M&A. Approach: A case study approach is employed, using descriptive and comparative analysis methods to examine two banks—ABI Bank and OTP Bank—before and after M&A transactions. Financial data were sourced from official banking reports and databases. Results: Findings show that OTP Bank experienced substantial improvements in profitability and operational indicators post-merger, whereas ABI Bank displayed limited change due to data limitations and internal constraints. Implications: The results are relevant to academics studying post-M&A performance, policymakers evaluating the banking sector’s stability, and bank administrators planning strategic growth. Value: This paper adds value by providing country-specific empirical evidence on M&A impacts in the Albanian banking sector, an under-researched region, and offers practical implications for enhancing post-merger integration and performance.